Getting ready to negotiate : the Getting to yes workbook / Roger Fisher; Danny Ertel - Fisher, Roger
Based on the philosophy and advice presented in Getting to Yes - be prepared, negotiate interests not positions, understand the other side's interests, and work together - this is the tool that will help each person design the negotiating strategy that is best for him or her in any given situation. Getting Ready to Negotiate presents case studies, charts, and forms for blueprinting a personalized negotiating strategy, one that is certain to make negotiating situations more productive and profitable."--Jacket.